Pemberdayaan Unit Produksi Program Keahlian Pemasaran âToko Karista Sariâ di Sekolah Menengah Kejuruan - Sulistyorini, Esti (Jurnal Varidika: Varia Pendidikan, 2015)
The aim of research to describe: Empowerment in providing merchandise Production , distribution of merchandise and reporting results poduction units merchandise program marketing expertise Stores in Vocational High School 1 Surakarta. This study used qualitative methods. Data were collected through interviews, observation and documentation. The validity of the data using credibility. Results from this study are: 1) Empowerment in the supply of merchandise can be done by: getting from the sales, the grocery store, and congsinyasi Checking on goods that have been purchased and distributing of goods and correctly 2) Empowerment of distribution of goods can be done by: Human Resources and Facilities optimize existing infrastructure, designing organizational structures, systems Applying pick up the ball, and the Door to Door Sales Program. 3) Empowerment of reporting the sale of goods can be: for writing for all the transactions that occur ,reported to the head of the production unit and headmasterr regularly, distribution of profits based on the AD ART and giving rewards to the customers.